2017
DOI: 10.17850/njg96-4-05
|View full text |Cite
|
Sign up to set email alerts
|

Extension, hyperextension and mantle exhumation offshore Norway: a discussion based on 6 crustal transects

Abstract: In spite of its classification as `magmatic´, the rifted margin off Mid Norway evolved as a hyperextended margin in Late Jurassic and Cretaceous time, with a pre-breakup structural evolution that resembles that of magma-poor margins. Because the distal margin was not drilled to crystalline basement, considerable uncertainty exists with respect to the distribution of lithologies at depth. In this contribution, we discuss the implications of various scenarios for deep-seated lithologies and evaluate the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 54 publications
0
43
2
Order By: Relevance
“…The density expected at the level of the ULCB is so high (3,200 kg/cm 3 ) and so massive that we disregarded the possibility of preserved deep sediments at that level. This is in contradiction with recent alternative assumptions from Osmundsen et al (). Shallow magnetic source estimations (Figure b) also support the presence of magnetic (basement) rock at 10–15 km and accordingly cannot easily explain the presence of Mesozoic sediments at that level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The density expected at the level of the ULCB is so high (3,200 kg/cm 3 ) and so massive that we disregarded the possibility of preserved deep sediments at that level. This is in contradiction with recent alternative assumptions from Osmundsen et al (). Shallow magnetic source estimations (Figure b) also support the presence of magnetic (basement) rock at 10–15 km and accordingly cannot easily explain the presence of Mesozoic sediments at that level.…”
Section: Discussioncontrasting
confidence: 99%
“…The density expected at the level of the ULCB is so high (3,200 kg/cm 3 ) and so massive that we disregarded the possibility of preserved deep sediments at that level. This is in contradiction with recent alternative assumptions from Osmundsen et al (2016). Shallow magnetic source estimations Tectonics 10.1002/2017TC004655…”
Section: Potential Field Modeling Of the Regional Transect And Crustacontrasting
confidence: 77%
“…Along many rifted margins, the gross‐scale structure changes considerably along strike (e.g., Péron‐Pinvidic et al, ; Stica et al, ), as shown also for the Norwegian margin by many workers (e.g., Blystad et al, ; Faleide et al, ; Osmundsen et al, , ; Tsikalas et al, , ). However, many margins can be subdivided into domains that share fundamental structural‐morphological characteristics (Péron‐Pinvidic et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…Transect locations in Figure . For detailed descriptions of the transects and discussions of alternative interpretation scenarios see Osmundsen et al (). The margin architecture changes significantly from the south Møre to the Central Vøring basin.…”
Section: Introductionmentioning
confidence: 99%
“…The COT, where breakup volcanics are found, is bounded to the east by a 100‐ to 200‐km wide continental domain of highly extended crust (i.e., 2‐ to 12‐km thick). Low‐angle detachments, similar to the ones observed in the Iberia margin, are believed to control the coupled stretching of the crust and the subcontinental mantle, which may have become exhumed if extension had continued (Osmundsen et al, ; Osmundsen & Ebbing, ; Péron‐Pinvidic et al, ).…”
Section: Introductionmentioning
confidence: 98%